THE ROLE OF MADRASAH AND GLOBAL CHALLENGES - Qornain, Dzul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Madrasas have a responsibility to maintain and respect the religious and cultural identity of students. In facing the challenges of globalization that can result in cultural homogenization, madrasas can become places that promote deep understanding of one's own religion and culture, as well as respectful intercultural dialogue. Improving the Quality of Education Madrasas need to continue to strive to improve the quality of education provided. This involves developing curricula relevant to global challenges, training qualified teachers, and using innovative learning methods that encourage critical thinking, creativity and 21st century skills. Madrasah socio-economic empowerment can play a role in empowering students socially and economically. This can be done through developing life skills, learning entrepreneurship, and preparing students to contribute to sustainable community development. Apart from providing religious education, some madrasas also provide general education which includes subjects such as mathematics, science, languages, and history. Madrasas can also facilitate extracurricular activities and skills development programs for students